2018
DOI: 10.1111/1742-6723.12923
|View full text |Cite
|
Sign up to set email alerts
|

Emergency demand, repeat and frequent presentations by older patients in metropolitan Melbourne: A retrospective cohort study using routinely collected hospital data

Abstract: The rate of repeat and frequent PAGP-type presentations by older people decreased in 2012 compared with 2008, suggesting that initiatives implemented to reduce avoidable presentations may have had an effect. However, an increase in the rate of frequent non-PAGP-type presentations, predominately for acute exacerbation of cardiovascular and respiratory conditions, has important implications for planning future healthcare delivery; hence, the importance of initiatives such as the Health Care Home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Our results show that age over 65 was the most significant sociodemographic determinant of FP. Other studies have similarly found increased rates of FP in the elderly 5,7,22 . Although older patients are more likely to have chronic diseases requiring ongoing care, 17,22 this highlights the need for further research and interventions to improve care coordination between health services and aged care services 5 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our results show that age over 65 was the most significant sociodemographic determinant of FP. Other studies have similarly found increased rates of FP in the elderly 5,7,22 . Although older patients are more likely to have chronic diseases requiring ongoing care, 17,22 this highlights the need for further research and interventions to improve care coordination between health services and aged care services 5 .…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have similarly found increased rates of FP in the elderly. 5 , 7 , 22 Although older patients are more likely to have chronic diseases requiring ongoing care, 17 , 22 this highlights the need for further research and interventions to improve care coordination between health services and aged care services. 5 Previous literature has shown evidence for case management 20 and enhanced geriatric outreach services such as Hospital in the Nursing Home.…”
Section: Discussionmentioning
confidence: 99%
“…Lowthian et al . found an increase in non‐potentially avoidable GP type ED presentations when examining inappropriate ED presentations in patients over the age of 70 years, with most related to cardiovascular or respiratory illness . A recent Western Australian study demonstrated the receipt of palliative home care nursing significantly reduced the rate of both lower acuity and higher acuity ED presentations .…”
Section: Discussionmentioning
confidence: 99%
“…Group 1 will receive the ‘HOW R U?’ intervention over the telephone. We have attempted to replicate the intervention as it was delivered in the previous trial 47 56. ‘HOW R U?’ trained volunteer-peers provide strength-based support sessions weekly over the phone for 12 weeks.…”
Section: Methods and Analysismentioning
confidence: 99%